Analisis Manajemen Sumber Daya Manusia Pada Budaya Kerja Terhadap Lama bekerja dan Kegiatan Pembinaan - Denok Mugi Hidayanti (Mathematics Education Study Program, 2024)
This study aims to analyze the relationship between work culture, which is influenced by length of service, and coaching activities. Using a quantitative approach, this study involves statistical analysis with the help of JASP software to determine if there is a relationship between these variables. The variables studied include length of service and coaching (as independent variables), and work culture (as the dependent variable). The results of the analysis showed that the data on work culture, length of service, and coaching activities had a normal distribution and showed a linear pattern in the graph. However, together, these three variables did not have a significant effect with a significant value > 0.001. In addition, when analyzed individually, length of service and coaching also had no significant impact on work culture. These findings indicate that, although these variables play an important role in the school environment, they did not influence each other in the context of this study. Further research is needed to explore other factors that may influence the relationship.